Influences of relative deprivation on health inequality of rural residents in China: A moderated mediation model - Tao, ChunHai; Xu, Jun; Tao, RuoYan; Wang, ZiYu; Li, JiaYi (Frontiers in Psychology, 2022)
Analyzing the relationship between individual relative deprivation and rural residents’ health inequality is a deepening of the research on the social impact of individual relative deprivation. On the theoretical basis of the absolute and relative income hypothesis, using the data of China Family Panel Studies in 2018, taking other residents in the village as the reference group, this paper selects the relative income deprivation and absolute income to comprehensively quantify the generalized impact of farmers’ income gap, introduces the psychological capital guidance mechanism, and constructs a moderated-mediation model for the impact of relative deprivation on the health inequality of rural residents in China from the three dimensions of self-assessment of health, mental health and physical health. The estimation results of the multi-layer model show that the relative income deprivation of rural residents has a significant impact on health inequality, among which the impact of mental health is the strongest. Compared with physical health, the mediated transmission of psychological capital has a more significant impact between the relative deprivation of rural residents and mental health. Compared with low-income groups, high-income residents can better alleviate the negative effect of income relative deprivation on psychological capital poverty and health inequality, and the regulatory effect on physical health is most significant. Therefore, China can improve the health of the rural poor through fiscal policies such as improving the tax system and strengthening the supervision of various government funds.